Results of the 2nd Scientific Workshop of the ECCO (III): basic mechanisms of intestinal healing - Rieder, Florian; Ehehalt, Robert (Journal of Crohn's and Colitis, 2012)
Abstract. The second scientific workshop of the European Crohn's and Colitis Organization (ECCO) focused on the relevance of intestinal healing for the disease